MicroRNA-100 and microRNA-21 as markers of survival and chemotherapy response in pancreatic ductal adenocarcinoma UICC stage II. Issue 1 (December 2015) - Dhayat, Sameer; Abdeen, Baha; Köhler, Gabriele; Senninger, Norbert; Haier, Jörg; Mardin, Wolf
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) remains a highly chemoresistant tumor entity for which no reliable molecular targets exist to predict or influence the success of chemotherapy. Recently, we identified a panel of microRNAs associated with induced gemcitabine chemoresistance in human PDAC cell lines. This clinical study evaluates these microRNAs and associated molecular markers as prognostic markers of outcome in 98 PDAC patients Union Internationale Contre le Cancer (UICC) stage II undergoing curative surgery with adjuvant gemcitabine chemotherapy. The primary end points of this study are recurrence-free survival and overall survival. Results Poor response to chemotherapy was significantly correlated to overexpression of microRNA-21 (p  = 0.029), microRNA-99a (p  = 0.037), microRNA-100 (p  = 0.028), and microRNA-210 (p  = 0.021) in tissue samples of PDAC patients UICC stage II. Upregulation of these microRNAs was associated with a significantly shorter overall survival and recurrence-free survival (p  < 0.05). Overexpression of phosphatase and tensin homolog (PTEN) (p  = 0.039) and low expression of multidrug resistance (MDR)-1 (p  = 0.043) and breast cancer resistance protein (BCRP)-1 (p  = 0.038) were significantly correlated to improved response to adjuvant chemotherapy. Adjuvant gemcitabine treatment (p  < 0.0001) and low tumor grading (p  = 0.047) were correlated to better outcome. MicroRNA-100, microRNA-21, and its targets PTEN and MDR-1 were independent factors of survival in multivariate analysis. Conclusions Multivariate survival analyses identified microRNA-21 and microRNA-100 as unfavorable prognostic factors in resected and adjuvant treated PDAC UICC stage II patients.